CANÁLISE COMPARATIVA DA AIDS: ANÁPOLIS VERSUS GOIÁS (2019-2023) (CIPEEX, 2026)
Introduction: The municipality of Anápolis stands out as one of the main epicenters of the AIDS epidemic in Goiás. However, beyond isolated description, it is essential to statistically compare the municipality with the state average in order to quantify the relative risk and understand regional inequalities. Objective: To compare AIDS incidence and prevalence rates in Anápolis and in the state of Goiás from 2019 to 2023, analyzing disparities and their socio-epidemiological determinants. Method: A comparative, descriptive, and analytical study based on secondary data from the Notifiable Diseases Information System (SINAN). Incidence and prevalence rates per 100,000 inhabitants were calculated. Statistical analysis employed the Student’s t-test for mean comparison, considering p < 0.05 as the significance level. Results: Anápolis showed consistently higher incidence rates than state averages between 2019 and 2022, with values around 12 cases/100,000 inhabitants, compared to 7–9/100,000 at the state level. Statistical testing confirmed significance (p < 0.05). Regarding cumulative prevalence, Anápolis recorded 47.0 cases/100,000, 38.5% higher than the state average (33.93/100,000), also a statistically significant difference. Conclusion: Anápolis presents a higher epidemiological risk than the state average, both in incidence and prevalence, reflecting not only greater detection but also a genuinely more intense epidemic. Factors such as population mobility, social vulnerabilities, late diagnosis, and underreporting contribute to this disparity. These findings reinforce the need for municipality-specific territorial policies.
Keywords: HIV; AIDS; epidemiology; regional comparison